EFFECT OF DIFFERENT FEEDS AND WATER SALINITIES ON THE CYST PRODUCTION OF BRINE SHRIMP, ARTEMIA SP. - Vartak, V. R.; Joshi, V. P. (Journal of Indian Fisheries Association, 2015)
Effect of different feeds and salinities on cyst production in Artemia sp.was studied. Among the 12 different feeds used, ragi powder suspensionshowed the best growth and cyst production. A wide range of salinity from90 to 210 %o was used to study its effect on cyst production. Among all thesetreatments, 130 %o salinity was found suitable for induction of oviparity andcyst production in the San Francisco Bay strain of Artemia sp.Keywords : Artemia sp., oviparity, cyst, feeds, reproductive capacity